Activité anti-toxoplasmose, screening phytochimique et étude de la cytotoxicité de l’extrait éthanolique 70% de Hunteria eburnea Pichon (Apocynaceae) - Djeneb, Camara; Kiyinlma, Coulibaly; Yao, Kanga; Cordelia, Bisanz; Marie-France, Delauw; Noël, Zirihi Guédé (European Scientific Journal, ESJ, 2018)
Hunteria eburnea is a medicinal plant used in traditional medicine in the Sassandra Region (Ivory Coast) in the treatment of malaria and skin diseases. The aim of this study is to study the inhibitory effect of 70% ethanolic extract of Hunteria eburneaa stem bark on Toxoplasma gondii, a protozoan parasite such as Plasmodium falciparum that causes toxoplasmosis. The 70% ethanolic extract was obtained from the parts of the plant that are used by traditional health practitioners in the Haut-Sassandra Region (Ivory Coast).The 70% ethanolic extract of Hunteria eburnea stem bark revealed high anti-Toxoplasma gondii activity with an estimated IC50 of 0.72 mg / mL and no cytotoxicity to HFF cells. (Human Foreskin Fibroblasts). Also, the phytochemical screening of this extract revealed the presence of sterols / triterpenes as well as alkaloids. This result indicates a promising source of new anti-Toxoplasma drugs from Hunteria eburnea, a West African medicinal plant.